Answer:
The probability is ![2.7327 \times 10^{-9}](https://tex.z-dn.net/?f=2.7327%20%5Ctimes%2010%5E%7B-9%7D)
Step-by-step explanation:
The probability of guessing correctly, P = 0.54
Probability of not guessing correctly, q = 1 – P
q = 1 – 0.54 = 0.46
Number of trials, n = 32
Now calculate the probability that Mr. Taylor will pick 32 correctly in first round of the game.
Below is the calculation using binomial distribution.
![Probability = \left ( _{k}^{n}\textrm{} \right )P^{k}(1-P)^{(n-k)} \\= \left ( _{32}^{32}\textrm{} \right )0.54^{32}(0.46)^{(32-32)} \\= 0.54^{32} \\= 2.7327 \times 10^{-9}](https://tex.z-dn.net/?f=Probability%20%3D%20%5Cleft%20%28%20_%7Bk%7D%5E%7Bn%7D%5Ctextrm%7B%7D%20%5Cright%20%29P%5E%7Bk%7D%281-P%29%5E%7B%28n-k%29%7D%20%5C%5C%3D%20%5Cleft%20%28%20_%7B32%7D%5E%7B32%7D%5Ctextrm%7B%7D%20%5Cright%20%290.54%5E%7B32%7D%280.46%29%5E%7B%2832-32%29%7D%20%5C%5C%3D%200.54%5E%7B32%7D%20%5C%5C%3D%202.7327%20%5Ctimes%2010%5E%7B-9%7D)
A^2 + b^2 = c^2
base lines: home to first is a, first to second is b, home to second is c.
90^2 + 90^2 = c^2
or
![\sqrt{ {90}^{2} + {90}^{2} } = c](https://tex.z-dn.net/?f=%20%5Csqrt%7B%20%7B90%7D%5E%7B2%7D%20%20%2B%20%20%7B90%7D%5E%7B2%7D%20%7D%20%20%3D%20c)
![c = 127.28](https://tex.z-dn.net/?f=c%20%3D%20127.28)
...approximately
Answer:
Did you ever figured it out?
Step-by-step explanation:
?
![(8a^{-3})^{\frac{-2}{3}} = \frac{a^2}{4}](https://tex.z-dn.net/?f=%288a%5E%7B-3%7D%29%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%3D%20%5Cfrac%7Ba%5E2%7D%7B4%7D)
<em><u>Solution:</u></em>
<em><u>Given that,</u></em>
![(8a^{-3})^{\frac{-2}{3}](https://tex.z-dn.net/?f=%288a%5E%7B-3%7D%29%5E%7B%5Cfrac%7B-2%7D%7B3%7D)
We have to write in simplest form
<em><u>Use the following law of exponent</u></em>
![(a^m)^n = a^{mn}](https://tex.z-dn.net/?f=%28a%5Em%29%5En%20%3D%20a%5E%7Bmn%7D)
Using this, simplify the given expression
![(8a^{-3})^{\frac{-2}{3}} = 8^{\frac{-2}{3}} \times a^{ -3 \times \frac{-2}{3}}\\\\Simplifying\ we\ get\\\\(8a^{-3})^{\frac{-2}{3}} = 8^{\frac{-2}{3}} \times a^2\\\\We\ know\ that\ 8 = 2^3\\\\Therefore\\\\(8a^{-3})^{\frac{-2}{3}} =2^3^{\frac{-2}{3}} \times a^2\\\\(8a^{-3})^{\frac{-2}{3}} =2^{-2} \times a^2\\\\(8a^{-3})^{\frac{-2}{3}} = \frac{a^2}{4}](https://tex.z-dn.net/?f=%288a%5E%7B-3%7D%29%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%3D%208%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%5Ctimes%20a%5E%7B%20-3%20%5Ctimes%20%5Cfrac%7B-2%7D%7B3%7D%7D%5C%5C%5C%5CSimplifying%5C%20we%5C%20get%5C%5C%5C%5C%288a%5E%7B-3%7D%29%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%3D%208%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%5Ctimes%20a%5E2%5C%5C%5C%5CWe%5C%20know%5C%20that%5C%208%20%3D%202%5E3%5C%5C%5C%5CTherefore%5C%5C%5C%5C%288a%5E%7B-3%7D%29%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%3D2%5E3%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%5Ctimes%20a%5E2%5C%5C%5C%5C%288a%5E%7B-3%7D%29%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%3D2%5E%7B-2%7D%20%5Ctimes%20a%5E2%5C%5C%5C%5C%288a%5E%7B-3%7D%29%5E%7B%5Cfrac%7B-2%7D%7B3%7D%7D%20%3D%20%5Cfrac%7Ba%5E2%7D%7B4%7D)
Thus the given expression is simplified